Single molecule Raman detection of enkephalin on silver colloidal particles. Issue 3 (2004) - Kneipp Kneipp, Katrin Katrin; Kneipp Kneipp, Harald Harald; Abdali Abdali, Salim Salim; Berg Berg, Rolf W. Rolf W.; Bohr Bohr, Henrik Henrik
Abstract : Enkephalin, an endogeneous substance in the human brain showing morphine‒like biological functions, has been detected at the single molecule level based on the surface‒enhanced Raman signal of the ring breathing mode of phenylalanine, which is one building block of the molecule. For enhancing the Raman signal the enkephalin molecules have been attached to silver colloidal cluster structures. The experiments demonstrate that the SERS signal of the strongly enhanced ring breathing vibration of phenylalanine at 1000 cm −1 can be used as "intrinsic marker" for detecting a single enkephalin molecule without using a specific label molecule. The reported result suggests the use of the phenylalanine 1000 cm −1 SERS line as spectroscopic signature for monitoring single proteins containing this amino acid as a building block.